Tinjauan Yuridis Joint Custody Pasca Perceraian Dalam Putusan Mahkamah Syar’iyah Idi dan Aceh - Nasution, Saphira Husna; Yazid, Imam; Iwan, Iwan (Jayapangus Press, 2025)
This article examines the practice of joint custody after divorce from an Islamic legal perspective through a legal analysis of two Sharia Court decisions, namely the Idi Sharia Court and the Aceh Sharia Court. The purpose of this study is to assess the legal basis for joint custody and to compare the legal considerations used in the two decisions. This research employs a normative legal approach using case study and conceptual analysis methods. The results of the study show differences in legal reasoning: the Idi Sharia Court took a progressive approach by applying a joint custody model through the division of roles between both parents, while the Aceh Sharia Court took a conservative approach by prioritizing the psychological stability of the child and granting sole custody to the mother. This comparison confirms that although both are based on the principles of the best interests of the child and maqāṣid al-syarī‘ah, their implementation results in different rulings.